2020
DOI: 10.1029/2020jb019738
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Potential Tomography of a Deep‐Sea Polymetallic Sulfide Deposit on Southwest Indian Ridge

Abstract: Deep-sea polymetallic sulfides associated with hydrothermal systems are considered a potential viable resource for base and precious metals. The Southwest Indian Ridge (SWIR, Indian Ocean) hosts active and inactive hydrothermal systems. Inactive hydrothermal fields are more abundant than active fields but are difficult to remotely characterize. We report a deep-sea self-potential investigation to locate inactive ore deposits at the Yuhuang hydrothermal field on the ultraslow-spreading SWIR. A horizontal array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Migrating electrons produce current in SMS deposits, creating spontaneous "geobattery" (Sato & Mooney, 1960). Seafloor self-potential surveys have shown that SMS deposits in inactive hydrothermal have strong electric anomalies (Szitkar et al, 2021;Zhu et al, 2020) and therefore confirm the existence of galvanic reactions in SMS deposits. Laboratory simulations have verified that galvanic reactions can accelerate the oxidation rates of sulfides (Knight et al, 2018).…”
Section: 1029/2022gc010368mentioning
confidence: 93%
“…Migrating electrons produce current in SMS deposits, creating spontaneous "geobattery" (Sato & Mooney, 1960). Seafloor self-potential surveys have shown that SMS deposits in inactive hydrothermal have strong electric anomalies (Szitkar et al, 2021;Zhu et al, 2020) and therefore confirm the existence of galvanic reactions in SMS deposits. Laboratory simulations have verified that galvanic reactions can accelerate the oxidation rates of sulfides (Knight et al, 2018).…”
Section: 1029/2022gc010368mentioning
confidence: 93%
“…It should be noted that the electric data we present in this study were acquired as horizontal electrical field components. A self‐potential (SP) could either be derived by integration of electrical fields along the flight path (e.g., Zhu et al., 2020) or by deriving the self‐potential field from the measured electrical fields by means of a regularized optimization process (Constable et al., 2018). However, as self‐potentials are only a derived quantity from the measured electrical field components, we will mostly refrain from using them in the scope of this article, similar to the aforementioned authors, who also mostly rely on electrical fields in the display and interpretation of their marine datasets.…”
Section: Motivations For Developing a New Type Of Sensormentioning
confidence: 99%
“…To improve the reliability of the measurements, we recommend distortion-reducing options, partially inspired by successful Japanese and Chinese experiments (Kawada & Kasaya, 2017Zhu et al, 2020):…”
Section: An Opening To the Future: Possible Engineering Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, galvanometric and electromagnetic methods have been used for the exploration and assessment of SMS resources. These methods include the controlled source electromagnetic (CSEM) method, the direct current (DC) resistivity imaging method, the transient electromagnetic (TEM) method, and the passive self‐potential (SP) method (see case studies in Cairns et al., 1996; Constable et al., 2018; Galley et al., 2021; Gehrmann et al., 2019; Haroon et al., 2018; Ishizu et al., 2019; Kawada & Kasaya, 2018; Müller et al., 2018; Su, Tao, Shen et al., 2022; Szitkar et al., 2021; Zhu et al., 2020). However, ore bodies and metallic deposits are not always characterized by conductivity contrasts (Mao & Revil, 2016; Mao et al., 2016).…”
Section: Introductionmentioning
confidence: 99%